Indiscretions of an Italian Lover: Montgomery Clift, Masculinity, and Melodrama. (4th May 2019) - Gaglio, Sam
ABSTRACT: This article utilizes production documents found in the David O. Selznick Collection to explore the role of masculinity as it is constructed in Stazione Termini (1953). More specifically, it seeks to reframe Montgomery Clift, the film's lead actor, as an inetto : an inept masculine character who repeatedly submits to the commands of both Mary, his lover, and her adolescent nephew, Paul. Traditionally an archetype found in Italian comedy, Clift's performance exemplifies the role of the inetto in the context of melodrama. While the comedic inetto demands centre stage in its film, the melodramatic inetto is instead pushed into the periphery, queering the heteronormative representation of the male leading character and undermining traditional notions of masculinity. The production files reinforce this reading.